Impact of variety and seed priming on anaerobic germination-tolerance of rice (Oryza sativa L.) varieties in Sri Lanka - T. K. Illangakoon; E. S. Ella; A. M. Ismail; B. Marambe; R. S. K. Keerthisena; A. P. Bentota; S. Kulatunge (Tropical Agricultural Research, 2016)
Ability of some rice (Oryza sativa L.) genotypes to germinate and grow under submerged conditions where oxygen supply is limited provides an efficient mean for weed control in direct seeded rice. This study was conducted to screen 38 rice varieties to anaerobic germination (AG) tolerance and to identify the influence of hydro-priming on survival and physiological responses of germinated seeds. Seed paddy was sown on saturated soil and soil inundated with 10 cm of stagnant water (submerged) to estimate the survival scores at 21 days after seeding. Six varieties having high survival scores under submerged condition were selected and their seeds were hydro-primed for 24 hrs in the dark at room temperature (25 °C) and were sown in saturated and submerged (10 cm water level) conditions. Soluble sugars, starch and α-amylase of germinating seeds were extracted and a separate set was kept to count the survival score. Varieties including Bg 300, Bg 310 and At 308 had moderate level of tolerance to AG. Hydro-priming improved the survival of rice seeds to about 40%. The synthesis of soluble sugars, starch degradation and α-amylase activity increased by hydro-priming compared to non-primed seeds germinated under submerged condition. Survival rate correlated positively with soluble sugar (r = 0.74) and and α-amylase (r = 0.79) contents and negatively with starch content (r = -0.51) at p < 0.05. These results emphasized the importance of hydro-priming as a seed treatment to enhance anaerobic germination tolerance in rice.